1980
DOI: 10.1021/j100458a023
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium oxide monolayer catalysts. 3. A Raman spectroscopic and temperature-programmed reduction study of monolayer and crystal-type vanadia on various supports

Abstract: Vanadium oxide monolayer catalysts. 3. A Raman spectroscopic and temperature-programmed reduction study of monolayer and crystal-type vanadia on various supports Roozeboom, F.; Mittelmeijer-Hazeleger, M.C.; Moulijn, J.A.; Medema, J.; de Beer, V.H.J.; Gellings, P.J. Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
170
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(184 citation statements)
references
References 6 publications
13
170
0
Order By: Relevance
“…In the next regime (7-11 wt<>A,) the experiments show shielding of V atoms by additional V species without affecting the Al or 0 signal. The additional V atoms have an octahedral environment [20,21], which is consistent with the growth of a multilayered structure or lamellas as is shown in tigure 5. 7.c.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In the next regime (7-11 wt<>A,) the experiments show shielding of V atoms by additional V species without affecting the Al or 0 signal. The additional V atoms have an octahedral environment [20,21], which is consistent with the growth of a multilayered structure or lamellas as is shown in tigure 5. 7.c.…”
Section: Resultssupporting
confidence: 78%
“…Laser Raman spectroscopie experiments by Roozeboom et al [19,20] showed that three different species may be present on the catalyst: vanadate tetrahedra, two-dimensional polymerie octahedral clusters and at higher of the vanadium oxide supported on y-alumina (9.8 wt%) have been given by Bergeret et al [22] using RED (radial electron distribution). These results indicate that the structure of the supported vanadium oxide is different trom bulk vanadium pentoxide ( fig.…”
Section: Fig 52mentioning
confidence: 99%
“…To understand the correlation between structural and catalytic properties of dispersed vanadia, various techniques including infrared [16-18a,18b], Raman [19][20][21][22][23], UV-visible [16,17,20,24,25], solid-state 51 V NMR [21], and X-ray absorption spectroscopy [18,26] have been used. In several studies, XPS has been employed to study the dispersion and oxidation state of supported vanadia catalysts [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the dispersed vanadia on the titania support enhanced the crystallization of TiO 2 . 10,11 A phase transformation of anatase to rutile is normally expected at 1073 K for TiO 2 with trace of V 2 O 5 . 10 In the present study, the calcination temperature was 723 K, with no indication of the rutile phase (JCPDS PDF No 76-1941).…”
Section: Resultsmentioning
confidence: 99%